Making “Good” Choices: Social Isolation in Mice Exacerbates the Effects of Chronic Stress on Decision Making - Mudra Rakshasa, Arish; Tong, Michelle T. (Frontiers in Behavioral Neuroscience, 2020)
Chronic stress can impact decision-making and lead to a preference for immediate rewards rather than long-term payoffs. Factors that may influence these effects of chronic stress on decision-making are under-explored. Here we used a mouse model to investigate the changes in decision-making caused by the experience of chronic stress and the role of social isolation in exaggerating these changes. To test decision-making, mice were trained to perform a Cost-Benefit Conflict (CBC) task on a T-maze, in which they could choose between a high-reward, high-risk alternative and a low-reward, low-risk alternative. Mice were either housed in groups or alone throughout the experiment. Both groups of mice underwent a seven-day period of repeated immobilisation to induce chronic stress. Stress levels were confirmed using behavioural (open field test) and physiological (urine corticosterone ELISA) measures. We found a significant increase in frequency of high-risk decisions after exposure to chronic stress among both socially- and individually-housed mice. Crucially, socially-housed mice showed a significantly smaller increase in high-risk decision-making compared to singly-housed mice. These findings suggest that chronic stress leads to an increase in high-risk decision-making in mice, and that lack of social interaction may exacerbate this stress effect.